2000
DOI: 10.1246/cl.2000.1154
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Graphite Electrode for Lithium Ion Batteries in Mn and Co Additive Electrolytes

Abstract: Dissolution of Mn into an electrolyte from LiMn2O4 in Li ion cell is researched recently. To study an influence of the dissolved manganese species on performance of negative electrode, electrochemical behavior of graphite was investigated in LiClO4 solution containing Mn2+ by dissolving Mn(ClO4)2. During charging, manganese ions were firstly electroreduced on the electrode, followed by Li intercalation into graphite. Mn deposition was confirmed after charge-discharge test, furthermore, the reversible capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 11 publications
2
36
0
Order By: Relevance
“…This capacity fading mechanism also leads to a pronounced increase in the electrode's impedance. It is reported that the severe capacity loss is induced by the deposition of Mn ions dissolved out of the LiMn 2 O 4 electrode on the graphite-negative electrodes [11,12], as confirmed by further studies [13,14]. This is one of the reasons causing capacity fading.…”
Section: Introductionmentioning
confidence: 66%
“…This capacity fading mechanism also leads to a pronounced increase in the electrode's impedance. It is reported that the severe capacity loss is induced by the deposition of Mn ions dissolved out of the LiMn 2 O 4 electrode on the graphite-negative electrodes [11,12], as confirmed by further studies [13,14]. This is one of the reasons causing capacity fading.…”
Section: Introductionmentioning
confidence: 66%
“…The majority of cases documenting the dissolution of the electro-active metal ion have focused on LiMn 2 O 4 , where Mn-ions in the electrode are easily dissolved into the electrolyte by acids generated via oxidation of the solvent molecules, but the process can occur in any Li x MO y phase [51][52][53]. Migration of the dissolved species to the anode can have fatal effects on the functionality of the cell; their precipitation on the anode terminal destroys the passivation layer on the negative electrode and can lead to the formation of a plated layer [54]. However, dissolution can be prevented by applying an oxide coating on the nanoparticles to decrease the surface area and eliminate any side reactions [55].…”
Section: Shortcomings Of Nanostructured Electrodesmentioning
confidence: 99%
“…It has also been revealed that nanostructured electrode materials with poor adherence to the current collector will agglomerate during cycling; nano-SnSb undergoes successive agglomeration during Li-ion insertion and extraction, and experiences quick capacity fade as a result [71]. Inactive LiMO y phases with transition metal cations of lower oxidation are formed from redox reactions with solution species [54]; moreover, these compounds can be spontaneously delithiated under ambient conditions involving reactions with CO 2 [72]. Thus, the application of some electro-active materials may be limited due to the high processing costs associated with avoiding these secondary reactions and stability issues.…”
Section: Shortcomings Of Nanostructured Electrodesmentioning
confidence: 99%
“…However, a significant weakness of LiMn 2 O 4 is that the dissolution of Mn 2+ at low cathode potentials and the deposition of metallic Mn by the hydrofluoric acid (HF) on the surface of the anodes are responsible for the fast capacity fading of the cells, particularly at elevated temperatures [4][5][6]. Many methods have been developed to solve the problem such as the: (1) partial substitution of Mn with different transition metals [2,7,8] or partial substitution of O 2À anions with Cl À [9], (2) enhanced surface coatings [10][11][12] and (3) use of new lithium salts instead of LiPF 6 [13][14][15].…”
Section: Introductionmentioning
confidence: 99%